Intercultural management : a case-based approach to achieving complementarity and synergy - Franklin, peter, 1955-; Barmeyer, Christoph, 1967- (Palgrave Macmillan, 2016)
How can organizations and individuals manage intercultural challenges and benefit from diversity? Intercultural Management is about managing across cultures: the difficulties and opportunities it brings and the competencies needed to handle the situations and create solutions. Applying a constructive approach, this book demonstrates how cultural diversity can be used as a resource to generate synergy and complementarity. Bringing together a collection of innovative case studies on a wide range of management topics it examines the issues in international management, helping the reader to explore theory in the context of real-life situations. Key features: Includes contributions from leading academics and practitioners. [bullet] Helps the reader develop core management competencies. Presents authentic international case studies from a range of countries including central and Eastern Europe as well as the Asian economies. User-friendly structure with solutions on a dedicated companion website.